A three-layer mechanical model for the analysis of effects of pia matter on cortical folding. Issue 8 (19th July 2019) - Wang, Linlin; Yao, Jianyao; Ning, Huiming; Wu, Liangke; Sun, Dongyang; Hu, Ning
Abstract : Purpose: This paper aims to investigate the effects of the pia matter on cerebral cortical folding. Design/methodology/approach: A three-layer buckling simulation model composited by the white matter, gray matter and the pia matter is adopted to analyze the effect of the pia matter on cortical folding. The volume growth of brain tissues is simulated using thermal expansion. The effects of the pia matter growth rate, thickness and stiffness on cortical folding is investigated. Findings: The simulation results show that all of these three aforementioned factors of pia matter have obvious effects on cerebral cortical folding. Especially, the thickening of the pia matter may lead to cortical folding malformation such as polymicrogyria, which is in good agreement with the recent reported anatomical findings. Originality/value: The three-layer model in this paper composited by the white matter, gray matter and the pia matter is different from the usually used two-layer model only composited by the white matter and gray matter. This three-layer model has successfully validated the effect of the pia matter on cerebral cortical folding. The simulation results can explain the anatomical findings very well.